ISLAM LIBERAL PERSPEKTIF LEONARD BINDER DAN CHARLES KURZMAN - Maftuh Maftuh (MIYAH : Jurnal Studi Islam, 2019)
This article explains about the imbalance in the religious understanding of Muslims today. This is due to the too narrow mind set of Muslims in interpreting the sources of Islamic teachings. Often Muslims are trapped textually in interpreting the al-Qur’an. So that religious doctrine becomes stagnant. Most humans do not understand that they are given the potential for reason by God. The concept of Islamic Liberalism by Leonard Binder and Charles Kurzman present a perspective on interpreting Islam, where Islam should be interpreted contextually according to the era. The following article will explain briefly about liberal Islamic by focusing on the views or thoughts of Islamic Liberalism according to Leonard Binder and Charles Kurzman. Keyword: Islamic Liberalism, Islamic Thougth.